PhP-cure a mobile Philippine currency recognition aid for the visually impaired - Mercado, Tamara Cher R. (Southeastern Philippines Journal of Research and Development, 2014)
PHP-Cure is an Android-based mobile application that recognizes the value of Philippine currency using digital image processing. Specifically designed for the visually impaired, the user captures a single banknote using a smart phone's camera and the application speaks out the value of the banknote. The basic concept in determining the value of the banknote was through color differences since each Philippine currency is give a specific dominant color. By the use of Histogram Comparison, each banknote was created with a color value sets which served as the basis for comparison. To implement the voice prompt requirement of the study, the Text-to-Speech (TTS) API was used. The said API works by taking a string of text and reads it aloud. The same API is also responsible in directing the user on how to manipulate the app. PhP-Cure as a mobile application, was successfully designed and develop with an easy touch and hear interface that was found fitting for the condition of its intended users. The voice prompt provided by the application was found to be very effective in conveying the value of the Philippine currency captured by the user's smart phones and in directing its user on how to manipulate the application.